The Problem of Electrical Engineering Students in Learning Business English Speaking - Atsani Wulansari (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The ability of speaking in English is needed in this era. In dealing with that reason, English for Specific Purpose (ESP)becomes the compulsory course in every faculty in university. The material in ESP should meet the students need; therefore the lecturers should find the material which is appropriate to their students. One of material which is given in ESP is Business English. Business English is a part of ESP branch which gives vocabulary, text and communication in business area. The material in Business English may in a form of application letter and job interview.This paper tries to elaborate the students problems during the learning of Business English and to find out the factor of the problem.This study used qualitative method. The students of first semester in electrical engineering department were asked to write an application letter. Then, they made a role play video to practice a job interview within the group of 4-5 students with own position: interviewer, interviewee, and secretary. After that, they upload their video in YouTube. The data was collected through observation and writing technique. The researcher observed the role play video made by the students. Then, the researcher wrote the problem from that observation. The researcher then identified the problems found during the role play and found the factor of the problem. The data were analyzed using speaking assessment category by Brown (2004).Based on the analysis, there are some problems in four categories, namely grammar, vocabulary, fluency, and pronunciation. The students frequently made errors in terms of grammar, inadequate vocabulary or word choice, level of fluency, and errors in pronunciation. The problems occurred due to intralingual andinterlingual transfer.